1997
DOI: 10.1007/s002220050118
|View full text |Cite
|
Sign up to set email alerts
|

Geometry of Deligne cohomology

Abstract: The aim of this paper is to give a geometric interpretation of holomorphic and smooth Deligne cohomology. Before stating the main results we recall the definition and basic properties of Deligne cohomology.Let X be a smooth complex projective variety and let Ω r X be the sheaf of germs of holomorphic r-forms on X. The qth Deligne complex of X is the complex of sheaveswhere Z(q) = (2π √ −1) q Z ⊂ C, and Z(q) X is the constant sheaf on X associated with the group Z(q). The hypercohomology H * (X, Z(q) D ) of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(75 citation statements)
references
References 5 publications
0
75
0
Order By: Relevance
“…) is the one of the isomorphism classes of flat line bundles on M and H 2 (M, D (2)) is the third real Deligne cohomology group [6,10]. The local data of a gerbe c = (B i , A ij , g ijk ) satisfy the cocycle condition 2 D 2 c = 0 and equivalent local data differ by a coboundary D 1 β with β = (Π i , χ ij ) so that the elements of the hypercohomology group H 2 (M, D(2)) are in a one-to-one correspondence with stable isomorphism classes of gerbes.…”
Section: Local Description Of Bundle Gerbesmentioning
confidence: 99%
See 1 more Smart Citation
“…) is the one of the isomorphism classes of flat line bundles on M and H 2 (M, D (2)) is the third real Deligne cohomology group [6,10]. The local data of a gerbe c = (B i , A ij , g ijk ) satisfy the cocycle condition 2 D 2 c = 0 and equivalent local data differ by a coboundary D 1 β with β = (Π i , χ ij ) so that the elements of the hypercohomology group H 2 (M, D(2)) are in a one-to-one correspondence with stable isomorphism classes of gerbes.…”
Section: Local Description Of Bundle Gerbesmentioning
confidence: 99%
“…We shall call Γ the orbifold group. In a natural way, we may lift its action to the Abelian groups A n of (2.6)-(2.9) by defining 10) etc. This turns the complex K(D(2)) of (2.3) induced from the sheaf complex (2.5) into one of Γ-modules.…”
Section: Gerbes On Orbifolds and Group Cohomologymentioning
confidence: 99%
“…In [26] Theorem H , it is shown that for a smooth manifold M , the group H 4 (M, Z) is isomorphic to the group of isomorphism classes of smooth principal B 2 U (1)-bundles over M .…”
Section: Proof Note That There Exists a Diffeomorphismmentioning
confidence: 99%
“…For cohomology theories based on geometric or analytic cycles there are often alternative models. This applies in particular to ordinary cohomology whose smooth extension has various different realizations (see Cheeger and Simons [7], Gajer [12], Brylinski [2], Dupont and Ljungmann [8], Hopkins and Singer [14] and Bunke, Kreck and Schick [3]). The papers by Simons and Sullivan [21] or Bunke and Schick [5] show that all these realizations are isomorphic.…”
Section: Introductionmentioning
confidence: 99%